2010
DOI: 10.1097/ico.0b013e3181b11648
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Carmellose 0.5% Versus Hyaluronate 0.15% in Dry Eye: A Flow Cytometric Study

Abstract: Both artificial tears improve dry eye signs and symptoms and inflammatory markers expression, with significant better results in carmellose group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 13 publications
1
52
0
2
Order By: Relevance
“…In addition, the use of AT rinses the ocular surface of toxins and debris and may dilute the concentration of inflammatory cytokines and other proinflammatory molecules that have been found in the tears [11][12][13][14][15][16] (clinical studies level II/III). Via all these mechanisms, the frequent use of AT serves to reduce proinflammatory stimuli 17 (clinical studies level II). This proposed explanation of a positive role in the use of AT must be regarded as speculative and unproven, as neither basic science nor clinical studies of the use of AT in MGD have been published to substantiate the hypothesis.…”
Section: Evidence Supporting Available Treatment Options Artificial Lmentioning
confidence: 99%
“…In addition, the use of AT rinses the ocular surface of toxins and debris and may dilute the concentration of inflammatory cytokines and other proinflammatory molecules that have been found in the tears [11][12][13][14][15][16] (clinical studies level II/III). Via all these mechanisms, the frequent use of AT serves to reduce proinflammatory stimuli 17 (clinical studies level II). This proposed explanation of a positive role in the use of AT must be regarded as speculative and unproven, as neither basic science nor clinical studies of the use of AT in MGD have been published to substantiate the hypothesis.…”
Section: Evidence Supporting Available Treatment Options Artificial Lmentioning
confidence: 99%
“…Based on several studies on dry eye, preservative‐free topical lubrication is strongly recommended for patients who require long‐term eye‐drop administration . Examples of lubricants include carboxymethylcellulose 0.5–1%, carmellose sodium, or hyaluronic acid and petrolatum ointment at night if nocturnal lagophthalmos exists . Lipid‐containing eye drops are effective in improving symptoms and signs of dry eye and are particularly recommended in the presence of meibomian gland dysfunction .…”
Section: Complicationsmentioning
confidence: 99%
“…12 However other studies have shown that CMC shows more improvement than SH in tear breakup time and corneal staining, thus is more efficacious in treating DED. 26,27,28 Few studies have also revealed a greater reduction of inflammatory markers in the CMC group than in the HA group. 26,28 The combination of CMC and SH has high viscosity under low friction conditions (between blinking), thus stabilizing the tear film, but low viscosity under high friction conditions (during the blinking), thus it causes less adverse effects such as discomfort.…”
Section: Sodium Hyaluronate (Sh)mentioning
confidence: 99%
“…26,27,28 Few studies have also revealed a greater reduction of inflammatory markers in the CMC group than in the HA group. 26,28 The combination of CMC and SH has high viscosity under low friction conditions (between blinking), thus stabilizing the tear film, but low viscosity under high friction conditions (during the blinking), thus it causes less adverse effects such as discomfort. 30 The analysis comparing three formulations: CMC 0.5% and SH 0.1%, CMC 0.5% and SH 0.15%, and CMC 0.5% showed that the combination of CMC and SH was well tolerated and led to better treatment outcomes, causing less adverse effects when compared to one polymer alone.…”
Section: Sodium Hyaluronate (Sh)mentioning
confidence: 99%